(untitled) (Journal of Economics and Sustainability, 2020)
Even though fuel subsidy can give more profit to the fisheries sector, it also has drawbacks to the ecosystem that tends to lead to overcapacity. This study investigated the impact of fuel subsidies on the income of fishermen operating in Zone A and Zone B in Kedah and Perlis. Focus group discussions with fisherman association committees were conducted to understand the issues related to fuel subsidy. The regression analysis method was used to examine the relationship between the fishermenâ€™s monthly income and various explanatory variables, such as oil subsidy received by the fishermen, the incentive value of catch received, the monthly allowance, the location of fishing activity, and the socioeconomic background of fishermen. The result of the study revealed that Boat B fishermen gained more benefits from the implementation of fuel subsidized policy than Boat A fishermen because the former used larger boat sizes and better fishing gear. In addition, variables, such as fuel subsidy, operating costs, and duration of fishing hours, influenced fishermen’s income. Although fuel subsidies may contribute toward overfishing, fuel subsidy is still needed by small-scale fishermen since it can reduce the cost of fishing activities and thus increase their monthly income. This research indicates that it is important to understand the contribution of fuel as the total cost of fishing activities and how fuel subsidies can reduce these costs to improve the income of fishermen in the study area. Received 18 Apr 19. Revised 25 Oct 19. Accepted 5 Dec 19.